The Basic Methodical Approaches to the Organization of Trainings of the Specialized Anti-Epidemic Teams from Irkutsk Antiplague Institute - A. K. Noskov (Эпидемиология и вакцинопрофилактика, 2015)
The basic methodical approaches to the organization of trainings of the specialized anti-epidemic teams in the most approximate conditions to real extraordinary event are described. These trainings purpose the support of operative readiness of the mobile formations of Federal Service for Surveillance on Consumer Rights Protection and Human Wellbeing to work in an emergency epidemiological area